2021
DOI: 10.3390/biomedicines9040432
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, Pathophysiology, Molecular Mechanisms, and Clinical Management of Erectile Dysfunction in Patients Affected by Coronary Artery Disease: A Review

Abstract: Erectile dysfunction (ED) has been defined as the inability to attain or maintain penile erection sufficient for successful sexual intercourse. ED carries a notable influence on life quality, with significant implications for family and social relationships. Because atherosclerosis of penile arteries represents one of the most frequent ED causes, patients presenting with it should always be investigated for potential coexistent coronary or peripheral disease. Up to 75% of ED patients have a stenosis of the ili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 89 publications
1
37
0
1
Order By: Relevance
“…Literature is limited regarding the direct relationship between a family history of CAD and ED. Studies have shown an indirect relationship between ED and Family history of CAD [50] . However, this study, specifically reported that 117 (38.6%) out of 303 patients enrolled had a family history of premature CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Literature is limited regarding the direct relationship between a family history of CAD and ED. Studies have shown an indirect relationship between ED and Family history of CAD [50] . However, this study, specifically reported that 117 (38.6%) out of 303 patients enrolled had a family history of premature CAD.…”
Section: Discussionmentioning
confidence: 99%
“…entry system) string, InChIKey (IUPAC international chemical identifier), and tenta com-pounds are available in the Supplementary Table S1 and Supplementary Table S The phytochemical constituents determined in the extracts of leaves (Table 2) w classified as: Flavonoids (21); Coumarins and derivatives (11); Sesquiterpene lactones sesquiterpenoids (4); terpene lactones and terpenoids (3); organic acids (3); anthraq nones (2); eudesmanolides and derivatives (2); phytoprostane (3), phenolic acids (1), o ers (27). In the stems (Table 3), the phytochemical constituents were classified as: cou rins and derivatives (6); flavonoids (3); sesquiterpene lactones and sesquiterpenoids terpene lactones and terpenoids (3); organic acids (3); aromatic monoterpenoids (2); b zyl alcohols (2); alkyl-phenylketones (2); and others (18).…”
Section: Phytochemical Analysis Of the Ethyl Acetate Fraction Of Leav...mentioning
confidence: 99%
“…Furthermore, it is known that some risk factor could exacerbate ED, among obesity, metabolic syndrome, alcohol, and smoke [ 5 ]. Additionally, the main predominant neurotransmitter related to penile erection is nitric oxide (NO) released from noncholinergic fibers and the endothelium [ 6 ]. According to the guidelines of the American Urological Association and the European Urology Association, the management of ED as first strategy involves lifestyle modifications and second, the use of the phosphodiesterase type 5 inhibitor such as sildenafil [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern as recent dietary trends and projections suggest an increased consumption of ultraprocessed foods, sugar-sweetened foods and beverages, and vegetable oils in many regions of the world not traditionally associated with Western society [ 10 ]. Organic ED is a prevalent condition amongst men with obesity, which may develop in response to one or a combination of vascular, endocrine, and neurologic deficiencies [ 11 ]. Due to the multifactorial nature of the condition, challenges remain regarding efficacy assessment of interventional treatments and optimization of therapeutic approach [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic ED is a prevalent condition amongst men with obesity, which may develop in response to one or a combination of vascular, endocrine, and neurologic deficiencies [ 11 ]. Due to the multifactorial nature of the condition, challenges remain regarding efficacy assessment of interventional treatments and optimization of therapeutic approach [ 11 ]. As ED often precedes the development of cardiovascular disease, further understanding of the pathophysiology of ED in response to obesogenic environments may provide insights for advances in men’s health.…”
Section: Introductionmentioning
confidence: 99%